Associations between sleep parameters, non-communicable diseases, HIV status and medications in older, rural South Africans. Issue 1 (December 2018) - Gómez-Olivé, F.; Rohr, Julia; Roden, Laura; Rae, Dale; Schantz, Malcolm
Abstract As part of the Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI), we investigated sleep habits and their interactions with HIV or non-communicable diseases (NCDs) in 5059 participants (median age: 61, interquartile range: 52—71, 54% females). Self-reported sleep duration was 8.2 ± 1.6h, and bed and rise times were 20:48 ± 1:15 and 05:31 ± 1:05 respectively. Ratings of insufficient sleep were associated with older age, lack of formal education, unemployment, and obesity (p < 0.05). Ratings of restless sleep were associated with being older, female, having more education, being unemployed, and single. Hypertension was associated with shorter self-reported sleep duration, poor sleep quality, restless sleep, and periods of stopping breathing during the night (p < 0.05). HIV positive individuals not on antiretroviral treatment (ART) reported more nocturnal awakenings than those on ART (p = 0.029) and HIV negative individuals (p = 0.024), suggesting a negative net effect of untreated infection, but not of ART, on sleep quality. In this cohort, shorter, poor-quality sleep was associated with hypertension, but average self-reported sleep duration was longer than reported in other regions globally. It remains to be determined whether this is particular to this cohort, South Africa in general, or low- to middle-income countries undergoing transition.